The Effectiveness of a Group Kickboxing Training Program on Sarcopenia and Osteoporosis Parameters in Community-Dwelling Adults Aged 50–85 Years - Lin, Yen-An; Chen, Lee-Hwa; Chen, Fang-Ping; Wong, Alice May-Kuen; Hsu, Chih-Chan; Chen, Jau-Yuan (Frontiers in Medicine, 2022)
Background: Sarcopenia and osteoporosis are important health issues faced by older people. These are often associated with each other and share common risk factors and pathologic mechanisms. In the recently revised consensus of European Working Group on Sarcopenia in Older People, low muscle strength has been defined as the first characteristic of sarcopenia rather than loss in muscle mass, and walking speed has been stated as an indicator of severity of sarcopenia. It is believed that these markers of muscle function can be potentially reversed via exercise-based interventions. The purpose of this study was to evaluate the effects of kickboxing exercise training on parameters of sarcopenia and osteoporosis in community-dwelling adults. Methods: One hundred eligible subjects were randomized into an intervention group (n=50) with 76% females and control group (n=50) with 86% females. Both the intervention and control groups were provided with classroom lectures and personal consultations pertaining to sarcopenia and osteoporosis, whereas a 12-week kickboxing exercise training was arranged only for the intervention group. All anthropometric, physical performance, body composition and bone mineral density measurements along with participant completed questionnaire were conducted before and after the training period. Results: After 12 weeks, 41 participants in the intervention group and 34 participants in the control group completed the final assessments. There was no difference between the intervention and control groups in terms of basic demographic data. The BMI (+1.14%) of the control group increased significantly during the study period. The waist circumference (-6.54%), waist to height ratio (-6.57%), waist to hip ratio (-4.36%), total body fat (-1.09%), and visceral fat area (-4.6%) decreased significantly in the intervention group. Handgrip strength (+5.46%) and gait speed (+5.71%) significantly improved in the intervention group. The lean body mass increased by 0.35% in the intervention group and by 0.9% in the control group. The femoral neck bone mineral density (-1.45%) and T score (-3.72%) of the control group decreased significantly. The intervention group had more improvement in status of sarcopenia and osteoporosis over the control group. Finally, the intervention group had less deterioration in status of sarcopenia and osteoporosis compared to the control group.